DEVELOPMENT OF PERSONALITY MATURITY OF FUTURE SOCIAL TEACHERS - Didyk, Nataliia M. (Educological discourse, 2014)
In the article the features of development of personality maturity of social teachers are examined in the process of professional preparation; akmeologic technologies, active methods of forming experiment, are analyzed, meaningfulness of independent work of student is exposed, him subject position; the results of development of descriptions of maturity of personality are reasonable; recommendations are given in relation to development for the social teachers of personality maturity and forming professionally of meaningful descriptions in the process of professional preparation.